Layanan Penguasaan Konten dengan Teknik Symbolic Modelling untuk Meningkatkan Perilaku Prososial Siswa - Ana Rahmatun Khasanah; Eko Nusantoro; Maria Theresia Sri Hartati (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2019)
Mastery content service is one of the guidance and counseling topic that is quite familiar in Indonesia to facilitate participants mastering a current series of competences. The purpose of this study is to examine the effectiveness of mastery content service using symbolic modeling techniques to foster the student’s pro-social behavior. This study used the experimental design via one group pre-test and post-test, and involved 35 junior high school students. We build some examples videos that demonstrate pro-social behavior as supplementary material to enhance the mastering content services during 8 sessions. The results of this study prove that there was an increase in understanding of students' pro-social behavior after being given mastery content service with symbolic modeling techniques. The interesting thing in this study presents that there are discrepancies in some indicators of pro-social behavior indicated by students, where the highest increase occurs in behaviors giving support and the lowest increase in charitable behavior in others. We realize that increasing prosocial behavior experienced by students after getting treatment is quite much influenced by some situational characteristics, and events.